Empowering communities for sustainable stunting prevention: A comprehensive approach to enhance child nutrition and family health education - S. Sukardi; Durratun Nashihah; Ilham Nur Hanifan Maulana (Inovasi Kurikulum, 2024)
Stunting is a significant public health concern influenced by various factors, including education. Studies have shown that reducing the burden of stunting requires interventions that extend beyond focusing solely on children to reaching mothers and families to improve their living environment and nutrition. The purpose focuses on sustainable stunting prevention strategies in Malang City, Indonesia, to enhance child nutrition and family health. Stunting, a form of chronic malnutrition, has long-term consequences on children's growth, cognitive development, and overall health. We used the information from the NFHS 2019-2021 report on the National Family Health Survey. Addressing stunting in Malang requires a comprehensive approach that considers medical and nutritional aspects and factors like education, sanitation, environmental sustainability, and institutional capacity. By integrating these diverse elements into interventions and policies, Malang can work towards reducing stunting prevalence and improving the health and well-being of its population. AbstrakStunting adalah masalah kesehatan masyarakat yang signifikan, dipengaruhi oleh berbagai faktor, termasuk pendidikan. Penelitian telah menunjukkan bahwa mengurangi beban stunting membutuhkan intervensi yang melampaui fokus hanya pada anak-anak untuk menjangkau ibu dan keluarga untuk meningkatkan lingkungan hidup dan gizi mereka. Tujuannya berfokus pada strategi pencegahan stunting berkelanjutan di Kota Malang, Indonesia, untuk meningkatkan gizi anak dan kesehatan keluarga. Stunting, suatu bentuk kekurangan gizi kronis, memiliki konsekuensi jangka panjang pada pertumbuhan anak, perkembangan kognitif, dan kesehatan secara keseluruhan. Kami memanfaatkan informasi dari laporan NFHS 2019-2021 tentang Survei Kesehatan Keluarga Nasional. Penanganan stunting di Malang membutuhkan pendekatan komprehensif yang tidak hanya mempertimbangkan aspek medis dan gizi tetapi juga faktor-faktor seperti pendidikan, sanitasi, kelestarian lingkungan, dan kapasitas kelembagaan. Dengan mengintegrasikan beragam elemen ini ke dalam intervensi dan kebijakan, Malang dapat bekerja untuk mengurangi prevalensi stunting dan meningkatkan kesehatan dan kesejahteraan penduduknya.Kata Kunci: pendidikan kesehatan keluarga; peningkatan gizi anak; pencegahan stunting